The Effect of Organic and Inorganic Fertilizers on the Growth and Production of Curly Red Chili: Pengaruh Pemberian Pupuk Organik Dan Anorganik Terhadap Pertumbuhan dan Produksi Cabai Merah Keriting - Sri Rahma Tika; Hasfiah Hasfiah (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
Red chili (Capsicum annum L.) is one type of horticultural plant that is very important to be cultivated commercially. The high price of chili provides high benefits for farmers. However, one of the obstacles faced by farmers is low fruit productivity and a long harvest time will certainly reduce the profits of chili farmers. Fertilization is one of the important factors in the cultivation of red chili (Capsicum annum L.). This study aims to determine whether the application of organic fertilizers and inorganic fertilizers can increase the growth and production of red chili plants. This research be conducted in the experimental garden, Bukit Wolio Indah Village, Wolio District, Baubau City, from May to August 2019. This study used a completely randomized design (CRD) with a factorial pattern consisting of 3 replications. The first factor is chicken manure, namely a0 (control), a1 (chicken manure with a dose of 100 g / polybag), a2 (chicken manure at a dose of 200 g / polybag), and a3 (chicken manure at a dose of 300 g / polybag). ). Meanwhile, the second factor of NPK Phonska fertilizer is p1 (NPK Phonska fertilizer with a dose of 1 g / polybag), p2 (NPK Phonska fertilizer with a dose of 2 g / polybag), and p3 (NPK Phonska fertilizer with a dose of 3 g / polybag). The results of data analysis will be continued with the Honest Real Difference Test (BNJ). The responses observed were plant height (cm), number of flowers (tree flower-1), number of fruit (tree fruit-1), production (tree fruit-1), and weight of fresh fruit (g fruit-1). Based on the results of the study, the application of chicken manure and NPK Phonska fertilizer had a significant effect on height, number of flowers, number of fruits, plant production and plant fresh weight. The use organic fertilizers cannot substitute the use of inorganic fertilizers. Keywords: Red chili (Capsicum annum L.), Chicken manure, NPK Phonska.